Deficiência, conhecimento e aprendizagem: uma análise relativa à produção acadêmica sobre educação especial e currículo - Correia, Gilvane Belem (2016)
This research, of qualitative and bibliographic nature, had the objective to discuss the relationship between special education and curriculum, permeated by concepts such as disabilities, knowledge and learning. The theoretical basis is associated with the systems thinking through connections with scholars such as Gregory Bateson, Humberto Maturana, Francisco Varela and Fritjof Capra. The work also dialogues to the ideas of authors such as Boaventura de Sousa Santos, Philippe Meirieu, in addition to the curriculum studies. It sought further support from references such as the International Convention on the Rights of Persons with Disabilities, sponsored by the UN in 2007. The paths taken by academic research in education are investigated by relating special education and curriculum, trying to identify the aspects that have emerged as the most significant ones. 148 works were analyzed, including theses, dissertations and articles published in the CAPES Portal, Brazilian Digital Library of Theses and Dissertations - BDBTD, National ANPEd, South ANPEd and Redalyc, from 2009 to 2015. Among the emerging aspects of the research there are the emphasis on curriculum adaptations, adjustments, flexibilities that, by the way which they are being described and practiced, do not potentiate the access to knowledge of students with disabilities. As for the concepts perceived as underlying to the practices, the study identified the presence of concepts of disability as impairment, inability, immutable; vision on knowledge associated with an external dimension to the subject, as a perennial truth; concepts of learning as the ability to capture through the senses, to store in memory and to play as needed. Before such evidences, the possibility of problematizing the design of curricular adaptations is discussed, in the way researchers have presented them - individual, parallel and simplified curricula - from broader concepts and the resignification of disability, knowledge and learning. In that sense, the curriculum is conceived as a space-time of negotiation between cultures coming from the differences; disability as a social construct; knowledge as a production of meanings, always linked to power and in the plural (knowledges); and learning as an action of the subject on/with the environment. This perspective is based on the understanding that can be synthesized in the concept: accessibility to the curriculum.